The Effects of Digital Marketing, Entrepreneurship Orientation, and Product Innovation on Competitive Advantage and Its Impact on the Marketing Performance of Talas Bolu Sangkuriang in Bogor City - Rahayu Lestari; Tiara Pradani; Kumba Digdowiseiso (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research aims to investigate the effects of digital marketing, entrepreneurship orientation, and product innovation on competitive advantage and its impact on marketing performance of Talas Bolu Sangkuriang in Bogor city. Specifically, we focus on an analysis that improves the marketing performance and competitive advantage of Talas Bolu Sangkuriang in Bogor City. We utilize the Purposive Sampling technique, with as many as 100 respondents using a proportional random sample. The analytical method used is statistical-partial least squares using the SmartPLS 3.0 software analysis tool. The results showed that digital marketing had a positive and significant effect on competitive advantage. Similarly, product innovation generated a positive and significant result on competitive advantage. Meanwhile, entrepreneurial orientation produced an insignificant effect on competitive advantage. Similarly, digital marketing, entrepreneurial orientation, and product innovation had an insignificant effect on marketing performance. However, competitive advantage showed a positive and significant effect on marketing performance.